The socio-communicative abilities of infants in the first year of life: a longitudinal study - Aquino, Fabíola de Sousa Braz; Salomão, Nádia Maria Ribeiro (Paidéia (Ribeirão Preto), 2011)
This study identifies the primary socio-communicative abilities evidenced by infants in three points in their first year of life, and the different configurations in each age. Emphasis is given to the idea that understanding child socio-cognitive and communicative dimensions is essential to acquire a better understanding of the genesis of human development and language. Six mother-infant dyads participated in the study. Infants were observed in their homes for 40 minutes of free play at the ages of six, nine and 12 months of age. The results demonstrated that the socio-communicative abilities of the infants were reconfigured in each subsequent age, permitting us to identify, especially at the age of 12 months, a higher frequency of intentional communicative abilities. The empirical data obtained in this study contribute to a better understanding of infant social cognition in the first year of life, with a focus on the bidirectional nature of mother-child interaction.